Perfil dos empreendimentos de enconomia solidária: o caso 18ª FEICOOP - Prass, Raquel Marcele da Silva (2012)
The global economic scenario has undergone significant changes in recent years, due mainly to factors such as globalization, competitiveness and technological advances. Therefore, this research aims to identify the profile of social economy enterprises in the case study of the 18th State Fair of Cooperatives (FEICOOP) held annually in Santa Maria. This scenario involves economic aspects and the political, organizational, informational, commercial, cultural and social, among others, that relate in a dynamic way. From there, the knowledge is with the emergence of concepts fundamental to the determination of a new opportunity for social economy. In this sense, it highlights the social and scientific relevance of this work, as determining the profile of entrepreneurs to economic solidarity of the participants of the 18th FEICOOP is possible to ensure continuous improvement of processes involving the development and growth of economic enterprises in solidarity. By identifying this profile facilitates the development of actions necessary for the growth of these enterprises. Also, the definition of the profile directly assists workers and family members who survive this alternative to generating employment and income. The case study was developed through exploratory, descriptive and explanatory, and data collection was performed during days 8, 9 and 10 July 2011, in 18th FEICOOP. The results showed that women predominated, involvement of family consisting of entrepreneurs, especially in the craft as a major promoter of the solidarity economy, with little access to government resources and NGOs This view is necessary because some aspects passing irrelevant into account the regional analysis specific than are needed for growth and development of social economy. The exhibitors of the fair participants are from different Brazilian regions, specifying the overview of the economic solidarity of the organization before the fair. Still, showed that each development, with different cultures, we adopt a local development plan differentiated, depending on family income and number of unemployed in need of new economic activities.